2018
DOI: 10.1103/physreve.97.033311
|View full text |Cite
|
Sign up to set email alerts
|

Realizations of highly heterogeneous collagen networks via stochastic reconstruction for micromechanical analysis of tumor cell invasion

Abstract: Three-dimensional (3D) collective cell migration in a collagen-based extracellular matrix (ECM) is among one of the most significant topics in developmental biology, cancer progression, tissue regeneration, and immune response. Recent studies have suggested that collagen-fiber mediated force transmission in cellularized ECM plays an important role in stress homeostasis and regulation of collective cellular behaviors. Motivated by the recent in vitro observation that oriented collagen can significantly enhance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 93 publications
1
40
0
Order By: Relevance
“…Importantly, the outermost layer (TACS3) is defined by linear branches of collagen growing perpendicularly away from invasive breast tumors [1]. Within breast cancer literature, words like "aligned," "oriented," "organized," and "linear" can be found referring to a specific extracellular matrix (ECM) pattern of the invasive breast tumors [2][3][4]. Clinically, there is a well-established link between the collagen architecture of the primary tumor and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the outermost layer (TACS3) is defined by linear branches of collagen growing perpendicularly away from invasive breast tumors [1]. Within breast cancer literature, words like "aligned," "oriented," "organized," and "linear" can be found referring to a specific extracellular matrix (ECM) pattern of the invasive breast tumors [2][3][4]. Clinically, there is a well-established link between the collagen architecture of the primary tumor and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, as the cell contracts isotopically, the fibers attached to the cell surface are pulled towards the cell center. The pulling forces result in reā€orientation and alignment of successive fiber segments to form linear chainā€like structures (see Figure 2 e), whose extent (ā‰ˆ20 to 40 Ī¼m) is much larger than the average length of the fiber segment (ā‰ˆ2 to 5 Ī¼m), [14a,b, 17] representing the experimentally observed fiber bundles. It is found that such chainā€like structures (i.e., fiber bundles) carry the majority of the tensile forces generated by the cell, and the force on the fiber bundles decays much slower, with a scaling ā‰ˆ1/ r Ī² (with Ī²ā‰ˆ0.68), than that in a continuous elastic medium (with ā‰ˆ1/ r ) (see Figure 2 f).…”
Section: Resultsmentioning
confidence: 99%
“…To further test our hypothesis in explaining the observed contrast between circular and triangular tumors, we devise a multiscale computational model that takes into account the fibrous microstructure of the ECM (11,12) and nonlinear ECM mechanics (13)(14)(15), as well as cell motility directed by ECM mechanical cues (16)(17)(18)(19). In particular, in our simulations, the tumor diskoid is modeled as a 3D packing of (spherical) cells within a flat cylinder with a thickness of 100 mm (i.e., $4-5 cell lengths) (see Fig.…”
Section: Computational Modeling Demonstrates Geometric Dependence Of Tumor Invasivenessmentioning
confidence: 99%